Characterization of gut microbiota in very low birth weight infants with versus without bronchopulmonary dysplasia - Anucha Thatrimontrichai; Manapat Praditaukrit; Gunlawadee Maneenil; Supaporn Dissaneevate; Kamonnut Singkhamanan; Komwit Surachat (Clinical and Experimental Pediatrics)
Background Gut-lung crosstalk is a pathway involving interactions between the gastrointestinal, respiratory, and immune systems. The immune responses of the gut and lungs are intricately linked, and previous studies demonstrated that the gut microbiota can influence systemic immune responses in the respiratory system as well as bronchopulmonary dysplasia (BPD). Purpose To analyze the composition of the gut microbiota in very low birth weight infants with versus without BPD. Methods Secondary data from a previous randomized controlled trial were analyzed. Microbiomes were analyzed using QIIME 2 software. Gut microbiota diversity and abundance were compared between groups. Results Fifty-one neonates were classified into the BPD (n=24) and non-BPD (n=27) groups, between which no differences were noted in the alpha and beta diversities of the gut microbiota. In both groups, Proteobacteria, Gammaproteobacteria, and Klebsiella were the predominant phylum, class, and genus in gut microbiota, respectively. Enterococcus, Acinetobacter, Elizabethkingia, Clostridium sensu stricto 1, Bacteroides, Streptococcus, and Serratia were more abundant, whereas Klebsiella, Faecalibacterium, Escherichia-Shigella, Enterobacter, Bifidobacterium, Veillonella, Staphylococcus, and Enterobacteriaceae were less abundant in the BPD versus non-BPD group. Faecalibacterium, Roseburia, Clostridium, Eubacterium, and Coprococcus were significantly more abundant in the non-BPD versus BPD group. Conclusion The alpha and beta diversities of the gut microbiota did not differ significantly between the BPD and non-BPD groups. However, in terms of relative abundance, the presence of common respiratory pathogens was notable in the BPD group. Conversely, the non-BPD group had a significantly higher prevalence of anaerobic taxa known for their capacity to produce butyrate, a key component of postbiotics.